Outstanding animal studies in allergy II. From atopic barrier and microbiome to allergen-specific immunotherapy. Issue 3 (June 2017) - Jensen-Jarolim, Erika; Pali-Schöll, Isabella; Roth-Walter, Franziska
Abstract : Purpose of review: Animal studies published within the past 18 months were assessed, focusing on innate and specific immunomodulation, providing knowledge of high translational relevance for human atopic and allergic diseases. Recent findings: Allergic companion animals represent alternative models, but most studies were done in mice. Atopic dermatitis mouse models were refined by the utilization of cytokines like IL-23 and relevant skin allergens or enzymes. A novel IL-6 reporter mouse allows biomonitoring of inflammation. Both skin pH and the (transferable) microflora have a pivotal role in modulating the skin barrier. The microflora of the gastrointestinal mucosa maintains tolerance to dietary compounds and can be disturbed by antiacid drugs. A key mouse study evidenced that dust from Amish households, but not from Hutterites protected mice against asthma. In studies on subcutaneous and sublingual allergen-specific immunotherapy, much focus was given on delivery and adjuvants, using poly-lacto-co-glycolic particles, CpGs, probiotics or Vitamin D3. The epicutaneous and intralymphatic routes showed promising results in mice and horses in terms of prophylactic and therapeutic allergy treatment. Summary: In atopic dermatitis, food allergies and asthma, environmental factors, together with the resident microflora and barrier status, decide on sensitization versus tolerance. Also allergen-specific immunotherapy operates with immunomodulatory principles.